2000
DOI: 10.1097/00005768-200007000-00006
|View full text |Cite
|
Sign up to set email alerts
|

Expression of the inducible nitric oxide synthase (iNOS) in human leukocytes: responses to running exercise

Abstract: Our investigations revealed an increased expression of iNOS at the transcriptional and translational level in response to vigorous exercise. This reflects an inflammatory response and may contribute to an exercise-induced rise of endogenous nitric oxide production. It remains unclear if these effects serve an in-vivo immunoregulatory or cell-damaging role.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
31
2

Year Published

2002
2002
2014
2014

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(36 citation statements)
references
References 21 publications
3
31
2
Order By: Relevance
“…We recently showed that inducible nitric oxide synthase (iNOS), IL-6, and HSP27 are upregulated after exercise at mRNA and protein levels (15,16,44). It remains to be shown which role the upregulation of MAPKAP-K2 mRNA as demonstrated in this study may play for the posttranscriptional modification of these and possibly other substrates in exercise.…”
Section: Gene Expression Changes Not Attributable To Obvious Cellularmentioning
confidence: 64%
“…We recently showed that inducible nitric oxide synthase (iNOS), IL-6, and HSP27 are upregulated after exercise at mRNA and protein levels (15,16,44). It remains to be shown which role the upregulation of MAPKAP-K2 mRNA as demonstrated in this study may play for the posttranscriptional modification of these and possibly other substrates in exercise.…”
Section: Gene Expression Changes Not Attributable To Obvious Cellularmentioning
confidence: 64%
“…It is believed that this exercise effect is related to the upregulation of eNOS [10,29,35]. Although it has been reported that vigorous exercise induces iNOS expression in leukocytes [19], whether iNOS plays any role in the exercise effect on vascular cells has not been examined before. Previous studies suggest that vascular smooth muscle cells express the iNOS gene only when they are stimulated by cytokines or lipopolysaccharide [4,15].…”
Section: Discussionmentioning
confidence: 99%
“…47 In humans, skeletal muscle expresses eNOS and nNOS isoforms, in addition to mNOS, 48 a skeletal muscle-specific isoform resulting from alternative splicing of nNOS mRNA. 49 In addition to skeletal muscle and endothelial cells, 50 circulating leukocytes 51 produce NO that could also affect muscle function.…”
Section: The Possible Role Of Free Fatty Acids On Heat Production Vamentioning
confidence: 99%